Skin tags: A link between lesional mast cell count/tryptase expression and obesity and dyslipidemia - Samar Abdallah M Salem; Enas AS Attia; Wesam M Osman; Marwa A El Gendy (Indian Journal of Dermatology, 2013)
Background:The etiology of skin tags (STs) is not fully understood. A relation to diabetes mellitus and obesity was suggested. Few studies of possible mast cells (MCs) involvement were reported. Tyrptase is a mast cell mediator and a potent fibroblast growth factor. It may provide a molecular link between mast cell activation and fibrosis. Aims: The aim was to assess clinical and laboratory findings in patients with STs, and the possible link between obesity, dyslipidemia, and lesional MC count/tryptase expression. Materials and Methods: A total of 20 patients with STs were subjected to clinical examination, estimation of body mass index (BMI), fasting blood glucose (FBG), postprandial blood glucose (PPBG), serum cholesterol and triglycerides, abdominal ultrasound for fatty liver assessment, in addition to study of MCs through staining for MC tryptase in two skin biopsies; lesional and nonlesional (control). Results:All patients showed abnormally high BMI and hypertriglyceridemia, with abnormal sonographic pattern in 15 patients (75%). STs number positively correlated with the age of patients. STs showed significantly higher MC counts and tryptase expression, compared with control skin ( P < 0.001), with no correlation of the STs number or MC count with BMI, FBG, PPBG or serum cholesterol. Obese patients showed a significantly higher MC count than overweight and there was a positive correlation between MC count and serum triglycerides. Axilla and under breast STs showed a higher MC count compared with other sites. Conclusions:STs seem to be related to obesity and hypertriglyceridemia. MCs with their tryptase are possibly involved in pathogenesis of STs. MC count is related to the associated factors; obesity and serum triglycerides. MC tryptase expression is a reliable method for accurate tissue MC counting.